Impact of the cardiopulmonary resuscitation-related injuries on the prognosis after cardiac arrest. (25th November 2020) - Merino Argos, C; Marco Clement, I; Rosillo Rodriguez, S.O; Martin Polo, L; Arbas Redondo, E; Tebar Marquez, D; Poveda Pinedo, D.I; Velez Salas, A; Rodriguez Sotelo, L; Martinez Marin, L.A; Gonzalez Fernandez, O; Caro Codon, J; et al.
Abstract: Background: Cardiopulmonary resuscitation (CPR) manoeuvres involve vigorous compressions with the proper depth and rate in order to keep sufficient perfusion to organs, especially the brain. Accordingly, high incidences of CPR-related injuries (CPR-RI) have been observed in survivors after cardiac arrest (CA). Purpose: To analyse whether CPR-related injuries have an impact on the survival and neurological outcomes of comatose survivors after CA. Methods: Observational prospective database of consecutive patients (pts) admitted to the acute cardiac care unit of a tertiary university hospital after in-hospital and out-of-hospital CA (IHCA and OHCA) treated with targeted temperature management (TTM 32–34°) from August 2006 to December 2019. CPR-RI were diagnosed by reviewing medical records and analysing image studies during hospitalization. Results: A total of 498 pts were included; mean age was 62.7±14.5 years and 393 (78.9%) were men. We found a total of 145 CPR-RI in 109 (21.9%) pts: 79 rib fractures, 20 sternal fractures, 5 hepatic, 5 gastrointestinal, 3 spleen, 1 kidney, 26 lung and 6 heart injuries. Demographic characteristics and cardiovascular risk factors did not differ between the non-CPR-RI group and CPR-RI group. Also, we did not find differences in CA features (Table 1). Survival at discharge was higher in the CPR-RI group [74 (67.8%) vs 188 (48.3%); p<0.001]. Moreover, Cerebral Performance Category (CPC) 1–2 within a 3-month follow-up was significantly higher in the CPR-RI group [(71 (65.1%) vs 168 (43.2%); p<0.001; Figure 1]. Finally, pts who recieved blood transfusions were proportionally higher in the CPR-RI group [34 (32.1%) vs 65 (16.7%)]; p=0.004). Conclusions: In our cohort, the presence of CPR-RI was associated with higher survival at discharge and better neurological outcomes during follow-up. Funding Acknowledgement: Type of funding source: None